2022
DOI: 10.3390/diagnostics12061435
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circulating Collagen Turnover Biomarkers and Late Gadolinium Enhancement in Patients with Non-Ischemic Dilated Cardiomyopathy

Abstract: Background: Myocardial scarring is a primary pathogenetic process in nonischemic dilated cardiomyopathy (NIDCM) that is responsible for progressive cardiac remodeling and heart failure, severely impacting the survival of these patients. Although several collagen turnover biomarkers have been associated with myocardial fibrosis, their clinical utility is still limited. Late gadolinium enhancement (LGE) determined by cardiac magnetic resonance imaging (CMR) has become a feasible method to detect myocardial repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Assessing peptides associated with collagen synthesis alone does not seem to constitute a sufficient strategy to specifically detect cardiac fibrosis [ 112 , 113 ]. In a multiparametric approach combining PICP, PIIINP, cardiac fibrosis area determination, and imaging on dilated cardiomyopathy biopsies, a study reported that P1CP/LGE combination provided a sensitive tool to predict adverse cardiac outcomes and that patients positive for cardiac fibrosis presented higher levels of P1CP and LGE [ 112 , 113 , 114 ].…”
Section: Emerging Techniques For the Detection Of Cardiac Fibrosismentioning
confidence: 99%
“…Assessing peptides associated with collagen synthesis alone does not seem to constitute a sufficient strategy to specifically detect cardiac fibrosis [ 112 , 113 ]. In a multiparametric approach combining PICP, PIIINP, cardiac fibrosis area determination, and imaging on dilated cardiomyopathy biopsies, a study reported that P1CP/LGE combination provided a sensitive tool to predict adverse cardiac outcomes and that patients positive for cardiac fibrosis presented higher levels of P1CP and LGE [ 112 , 113 , 114 ].…”
Section: Emerging Techniques For the Detection Of Cardiac Fibrosismentioning
confidence: 99%
“…Revnic et al focused on the use of CMR imaging to detect myocardial replacement fibrosis in patients with nonischemic dilated cardiomyopathy (NIDCM) and sought to evaluate the association between collagen turnover biomarkers and replacement myocardial scarring by CMR and test their ability to predict outcomes in conjunction with LGE in patients with NIDCM [7]. They found that galectin-3 (Gal3), procollagen type I carboxyterminal pro-peptide (PICP), and N-terminal pro-peptide of procollagen type III (PIIINP) were significantly increased in LGE+ individuals and were directly correlated with LGE mass.…”
Section: Idcmmentioning
confidence: 99%